Corinthian currants finishing side-stream: Chemical characterization, volatilome, and valorisation through wine and baker's yeast production-technoeconomic evaluation. (16th April 2021) - Plioni, Iris; Bekatorou, Argyro; Mallouchos, Athanasios; Kandylis, Panagiotis; Chiou, Antonia; Panagopoulou, Eirini A.; Dede, Vasiliki; Styliara, Paraskevi
Highlights: Valorisation of Corinthian (Vostitsa) currants finishing side-stream (FSS) FSS is rich in sugars, volatiles, phenolics, organic acids and antioxidant phenolics. Wine (low temperature; immobilised yeast) and baker's yeast production from FSS. Wines had no methanol and higher levels of free terpenes and fermentation volatiles. Realistic and worthwhile investment for industrial wine/yeast production from FSS. Abstract: The industrial currants finishing generates a considerable amount of side-stream (FSS) with great potential for biotechnological exploitation. The chemical composition of FSS generated from the premium quality Vostitsa currants was studied. Its use for wine making (at low temperatures, using both free and immobilized yeast) combined with baker's yeast production (with minor nutrient supplementation), is also proposed. Analysis showed that FSS has a rich volatilome (including Maillard reaction/lipid degradation products), increased antioxidant capacity, and total lipid and phenolic contents, compared to the marketable product (currants). However, acidity levels and the presence of specific volatiles (such as acetate esters and higher alcohols) may be indicative of microbial spoilage. The wines made from FSS were methanol free and contained higher levels of terpenes (indicating hydrolysis of bound forms) and fermentation-derived volatiles, compared to FSS. A preliminary technoeconomic analysis for integrated wine/baker's yeast industrial production, showed that the investment is realistic and worthwhile.